Does continuous cropping of maize contribute to infestation with Johnsongrass (Sorghum halepense (L.) Pers.)? - Simic, Milena Slobodan; Dragičević, Vesna; Brankov, Milan; Šenk, Milena (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
Johnsongrass (Sorghum halepense (L.) Pers.) is a very common weed in maize fields in Serbia. Dense Johnsongrass infestations severely limit maize production, especially under continuous maize cropping. The key tool to manage this weed is to implement multiple control strategies when Johnsongrass is first observed and not to wait until it is firmly established.Experiments were conducted in the Maize Research Institute (MRI), Zemun Polje, Belgrade, in order to examine how economically driven continuous cropping of maize influences weed infestation, especially the distribution and abundance of Jonhsongrass, as well as maize productivity. The maize hybrid ZP 606 was grown in continuous cropping from 2009 to 2018 at a density of 59,500 plants ha-1. The experimental field was split into a part treated with the pre-emergence herbicide isoxaflutole + metolachlor (750 + 960 ga.i.) and untreated control. The level of complete weed infestation was evaluated 4-5 weeks after herbicide application by determining the number of weed individuals per species (NI), total fresh biomass (TB) and total dry weight (TDW) of all weeds and Johnsongrass fresh biomass (JB) and dry weight (JDW). Maize harvest index (HI) and grain yield (GY) were determined at the end of each growing period.All measured weed parameters were highly dependent on agro-meteorological conditions of the year, herbicide application and their interaction. On average, TDW was 760.7 g m-2 in the control plot, and 142.2 g m-2 in the treated plot, while Johnsongrass participated with 34.8% and 48.7%, respectively. Herbicide application reduced JDW by 77.6% on average, even though its biomass increased over the years. A regression analysis revealed that GY was negatively influenced by JDW (R2= - 0.094) in untreated control, while GY was higher with a lower JDW under herbicide treatment (R2=-0.4439). Continuous cropping of maize should be replaced with crop rotation in order to prevent Johnsongrass prevalence and to obtain higher crop productivity.
Keywords: Sorghum halepense, maize, cropping system, weed control